A spatial access method approach to continuous k-nearest neighbour processing for location-based services. (3rd February 2020) - Osborn, Wendy
In this paper, two strategies for handling continuous k-nearest neighbour queries for location-based services are proposed. CKNN1 and CKNN2 utilise a validity (i.e., safe) region approach for minimising the number of query requests that need to be send to the server. They also use a two-dimensional spatial access method for both validity region selection and in-structure searching. The latter feature ensures that new searches for a validity region are not required to begin from the root. An evaluation and comparison of both strategies is performed against repeated nearest neighbour search. Both random and exponentially distributed point sets are utilised. Results show that both approaches achieve significant performance gains, especially with respect to reducing the number of queries that must be sent from the client to the server.